National nutrition strategies that focus on maternal, infant, and young child nutrition in Southeast Asia do not consistently align with regional and international recommendations. (30th June 2020) - Nguyen, Tuan T.; Darnell, Ashley; Weissman, Amy; Cashin, Jennifer; Withers, Mellissa; Mathisen, Roger; Lapping, Karin; Mastro, Timothy D.; Frongillo, Edward A.
Abstract: We examined the consistency of national nutrition strategies and action plans (NNS) focusing on maternal, infant, and young child nutrition in Southeast Asia with regional and international recommendations. Between July and December 2017, we identified and extracted information on context, objectives, interventions, indicators, strategies, and coordination mechanisms from the most recent NNS in nine Southeast Asian countries. All NNS described context, objectives, and the following interventions: antenatal care, micronutrient supplementation during pregnancy, breastfeeding promotion, improved complementary feeding, nutrition in emergencies, and food fortification or dietary diversity. Micronutrient supplementation for young children was included in eight NNS; breastfeeding promotion during pregnancy and support at birth in seven; and school feeding, deworming, and treatment of severe acute malnutrition in six. All NNS contained programme monitoring and evaluation plans with measurable indicators and targets. Not all NNS covered wasting, exclusive breastfeeding, low birthweight, and childhood overweight. Strategies for achieving NNS goals and objectives were health system strengthening (nine), social and behaviour change communication (nine), targeting vulnerable groups (eight), and social or community mobilization (four). All addressed involvement, roles and responsibilities, and collaboration mechanisms among sectors and stakeholders. There was a delay in releasing NNS in Indonesia, Myanmar, and the Philippines. In conclusion, although Southeast Asian NNS have similarities in structure and contents, some interventions and indicators vary by country and do not consistently align with regional and international recommendations. A database with regularly updated information on NNS components would facilitate cross‐checking completeness within a country, comparison across countries, and knowledge sharing and learning.